(untitled) (Eurasian Research Bulletin, 2024)
As organizations increasingly rely on structured databases powered by SQL to manage and manipulate vast amounts of critical information, the imperative of securing these repositories becomes paramount. This abstract provides an overview of the multifaceted landscape of SQL security and underscores its critical importance in the modern digital age